PRODUKTIVITAS KERJA PEGAWAI NEGERI SIPIL PADA BADAN KEPEGAWAIAN DAERAH (BKD) KABUPATEN INDRAGIRI HULU - Martha Wijayanti; Rusli Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Labor Productivity in the Civil Service Staffing Agency Indragiri Upstream Region.Productivity can basically be viewed from two dimensions , namely the dimension of individual and organizationaldimensions . Assessment of the productivity problem is not other people see the dimensions of productivity , especiallyin relation to the individual 's personality characteristics . In this context, understanding the essence of productivity is amental attitude that always has the view that quality of life should be better today than yesterday , and tomorrow shouldbe better than today ( Kusnendi , 2003:8 ) . The research was conducted at the Regional Employment Board Indragiri .The purpose of this study was to determine the Civil Servants Work Productivity in Regional Employment BoardIndragiri Hulu . This research uses descriptive qualitative method . Data were obtained from the interview data ,documentary studies , and field observations . Informants in this study were the parties relating to the Employee WorkProductivity using the snowball method . The results showed that Pproduktivitas Civil Servants working in the RegionalEmployment Board Indragiri Hulu is good enough . But employees should be able to increase the productivity of laborin order to what could be done better .Key Word: Produktivitas kerja, Motivasi, Pegawai Negeri Sipil